Industrial solutions for loading/unloading goods on a full electrical freight urban robotic vehicle. (2015) - Muscolo, Giovanni Gerardo; Leonardo, Luis Miguel De; Pietronave, Giorgio; Zoppi, Matteo; Molfino, Rezia
The authors present four industrial solutions for loading/unloading goods on a freight urban robotic vehicle, named FURBOT. The final design of the FURBOT vehicle allows the movement of two Euro Pallets 800 × 1, 200 mm (or FURBOT boxes with similar bottom part). Following a sustainable and efficient mobility approach, a robotic handling device must be designed and positioned on-board of the vehicle. The handling device must realise the loading-unloading operations on the right side of the vehicle and from the ground to the vehicle platform. Active suspensions of the FURBOT vehicle are designed to adapt the stiffness to the payload and by modifying the chassis height on the ground for travel and loading-unloading tasks.